The endoplasmic reticulum: A dynamic and well‐connected organelle. Issue 1 (January 2015) - Hawes, Chris; Kiviniemi, Petra; Kriechbaumer, Verena
Abstract The endoplasmic reticulum forms the first compartment in a series of organelles which comprise the secretory pathway. It takes the form of an extremely dynamic and pleomorphic membrane‐bounded network of tubules and cisternae which have numerous different cellular functions. In this review, we discuss the nature of endoplasmic reticulum structure and dynamics, its relationship with closely associated organelles, and its possible function as a highway for the distribution and delivery of a diverse range of structures from metabolic complexes to viral particles. <inline-graphic xlink:href="ark:/27927/pgh30vxbc52" content-type="jipb12297-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> Chris Hawes